Infrapatellar fat pad-derived MSC response to inflammation and fibrosis induces an immunomodulatory phenotype involving CD10-mediated Substance P degradation - Kouroupis, Dimitrios (Sci Rep, 2019)
The infrapatellar fat pad (IFP) serves as a reservoir of Mesenchymal Stem Cells (MSC), and with adjacent synovium plays key roles in joint disease including the production of Substance P (SP) affecting local inflammatory responses and transmitting nociceptive signals. Here, we interrogate human IFP-derived MSC (IFP-MSC) reaction to inflammatory and pro-fibrotic environments (cell priming by TNFα/IFNγ and TNFα/IFNγ/CTGF exposure respectively), compared with bone marrow-derived MSC (BM-MSC). Naïve IFP-MSC exhibit increased clonogenicity and chondrogenic potential compared with BM-MSC. Primed cells experienced dramatic phenotypic changes, including a sharp increase in CD10, upregulation of key immunomodulatory transcripts, and secreted growth factors/cytokines affecting key pathways (IL-10, TNF-α, MAPK, Ras and PI3K-Akt). Naïve, and more so primed MSC (both) induced SP degradation in vitro, reproduced with their supernatants and abrogated with thiorphan, a CD10 inhibitor. These findings were reproduced in vivo in a rat model of acute synovitis, where transiently engrafted human IFP-MSC induced local SP reduction. Functionally, primed IFP-MSC demonstrated sustained antagonism of activated human peripheral blood mononuclear cells (PBMC) proliferation, significantly outperforming a declining dose-dependent effect with naïve cohorts. Collectively, our in vitro and in vivo data supports cell priming as a way to enhance the immunoregulatory properties of IFP-MSC, which selectively engraft in areas of active synovitis/IFP fibrosis inducing SP degradation, resulting in a cell-based product alternative to BM-MSC to potentially treat degenerative/inflammatory joint diseases.